Rapid appraisal for ecosystem services assessment: applying the TESSA toolkit in Panti Recreational Forest, Johor - Mohd Nasir, Syazwanie Naziha; Mohd Nasir, Nurul Akmaniza; Mohd Hashim, Nor Hanisah; Kamarul Bahrain, Nawfal (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
This research project addresses the decrease in natural forest products and the importance of considering stakeholders’ perspectives in natural resource management efforts. The objectives of the project are to investigate the potential threats affecting the sustainability of Panti Recreational Forest as identified by stakeholders and to determine the perceived ecosystem services by the stakeholders in the area. The rapid appraisal approach from the Toolkit for Ecosystem Services Site-Based Assessment (TESSA) is applied to gather insights from the stakeholders before conducting a comprehensive analysis of ecosystem services. The project includes representatives from various stakeholder groups including the local authorities, professional groups, chalet operators, business operators, community leaders and local communities, with a total of 60 respondents. The project reveals that water management emerges as the most likely issue to occur shortly due to the daily water usage in the area, posing risks to the local community’s drainage system. Additionally, the project highlights that the recreational forest provides nature-based recreational opportunities for tourists and local visitors, thereby contributing to the economic sector of the region. By considering the perspectives of various stakeholder groups, effective strategies can be developed to address the identified threats and ensure the sustainable utilization of ecosystem services. Furthermore, the project underscores the positive impacts of the recreational forest in promoting sustainable recreational opportunities that safeguard the forest’s ecosystem services while supporting economic growth